Big data in the ICU: Experience in the Hospital Italiano de Buenos Aires - Astudillo, José (2017)
Intensive care represents the critical care setting of a hospital, where fundamental, precise, and fast decisions have to be made. These decisions will affect the outcome of the patients in a matter of few hours. The knowledge of the therapeutic interventions applied in this setting is evolving, thus the perspective of Big Data may provide a new paradigm in the ICU. The conformation of a multidisciplinary team is essential to develop Big Data in the ICU.